Morphological and Photometric Characteristics of Nearby Local Group Dwarf Galaxies - AL-Mashhadani, Layali Y. Salih; Abdullah, Ahmed H. (Iraqi Journal of Science, 2026)
The morphological and photometric characteristics of dwarf galaxies in the local group are key to understanding galaxy structure and evolution, providing insight into the properties of low-luminosity systems. However, their faint nature makes them challenging to observe, especially at greater distances. In this study, we examined the morphological classification, spatial distribution, and photometric properties of a sample of 33 nearby dwarf galaxies at approximately 2 kpc, using data from the Sloan Digital Sky Survey (SDSS-IV) data release 18 (DR18), to investigate how these galaxies are varying in terms of their colors, surface brightness, and structural features. Our results reveal notable trends in the relationship between morphology and distance for dwarf irregular (dIrr) and dwarf spheroidal (dSph) galaxies. We observe that dIrr galaxies are more dispersed and commonly found at greater distances, additionally, they are gas-rich galaxies with recent star formation, while dSph galaxies contain older stellar populations and tend to cluster closer to their host galaxies like the Miley Way. In general, we noticed that the dSph galaxies appear redder and fainter due to the intermediate and old age stars, and the containment of metal-rich stars, whereas the dIrr galaxies tend to be bluer and brighter, indicating the presence of younger stars which contain fewer heavy elements.